The Morpheme Analysis in the Hotel’s Greeting Card in Surabaya (JOSAR (Journal of Students Academic Research), 2024)
Morphemes, being the most fundamental meaningful grammatical entities within a language, play a significant role in enhancing the intricacy and depth of linguistic communication. Consequently, the analysis of morphemes serves as an indispensable instrument employed by linguists to deconstruct and comprehend these expressions, thereby offering valuable insights into the underlying structure, semantics, and cultural subtleties inherent in our communicative endeavors.The analysis of morphemes holds significance as it facilitates comprehension of the organization and semantics of words. Through the process of deconstructing words into their fundamental semantic components, one can acquire knowledge on the formation of words, their potential for modification, and their role in conveying meaning within sentences. The aforementioned analysis has the potential to enhance our linguistic abilities, understanding, and interpersonal exchange.The analysis of morphemes in a hotel's greeting card can yield vital insights into the linguistic nuances utilized to extend a warm welcome to guests, establish a favorable impression, and successfully convey crucial information.This research is going to find out the types of morpheme analysis , more specifically in the Hotel’s Greeting Card in Surabaya.The study utilizes a descriptive qualitative methodology. The research activities involve several distinct stages, including data collection, data analysis, and the subsequent conclusion, which is generated from the process of analyzing the data.Based on the findings, it was found out that there were 4 types of morpheme analysis, they were free root, bound root, free non root, and bound non root.